Metodologia heurística de alocação e dimensionamento de PV-STATCOM em sistemas de distribuição de média tensão: redução do investimento inicial e regulação dos níveis de tens - Alves, Zedequias Machado (2024)
The participation of Distributed Generation (DG) in the electrical distribution system has been growing in recent years, especially photovoltaic DG (FVGD). FVGD benefits the electrical system and the environment, but it also presents technical challenges and the need for adjustments. Maximizing the benefits and mitigating the challenges presented by FVGD is something widely discussed by researchers. Among the approaches, the possibility of using the idle capacity of photovoltaic inverters to maintain the grid voltage profile stands out, calling it PV-STATCOM. This research proposes a heuristic for sizing and allocating PV-STATCOM in the medium voltage (MV) distribution system. PV-STATCOM will assist with reactive compensation to maintain grid voltage levels within established limits. To determine the location and dimensioning of the PV-STATCOM, the idle capacity of the photovoltaic inverter is considered in power flow studies to be a synchronous compensator, that is, a PV-type bus. The methodology is applied to the idealized 10-bus and 33-bus Baran-Wu test systems. Initially, for the allocation of PV-STATCOM, the exhaustive search method is applied, and the results are compared with the particle swarm method (PSO), which is used as the basis for a heuristic proposal. The heuristic proposal is described in 10 steps, with the first seven steps being necessary for locating and sizing the PV-STATCOM, while the last three are required to apply the solution found to the system's daily power flow and make the required adjustments to the Volt-var curve. The methodology is compared with papers found in the literature, presenting superior results regarding the sizing of PV-STATCOM and exceptional results regarding technical losses. Installing PV-STATCOM at strategic points in the grid reduces the amount of reactive power required to maintain voltage levels within the desired limits, which results in lower investment.